2009
DOI: 10.1002/pola.23233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self‐organization properties of copolyurethanes based on perylenediimide and naphthalenediimide units

Abstract: A series of perylene and naphthalene diimide‐containing random copolyurethanes with different ratios of perylene/naphthalene diimide content was synthesized and characterized. Copolymerization improved the solubility of these rigid aromatic diimides, and the copolymers were soluble in common organic solvents like chloroform, tetrahydrofuran, and so forth. The absorption spectra of perylene‐based copolymers showed a red‐shifted peak at a wavelength of 557 nm corresponding to J‐type aggregates. For naphthalene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In 2009, Asha synthesized and characterized a series of naphthalene diimide‐containing copolyurethanes with different ratios of naphthalene diimide. It was found that fluorescence quenching happened with higher naphthalene incorporation, which indicated the presence of aggregates in the structure due to extensive π ··· π stacking of the aromatic core 11b. A similar fluorescence quenching mechanism was also reported in metal‐organic compounds 12a–12c.…”
Section: Resultssupporting
confidence: 63%
“…In 2009, Asha synthesized and characterized a series of naphthalene diimide‐containing copolyurethanes with different ratios of naphthalene diimide. It was found that fluorescence quenching happened with higher naphthalene incorporation, which indicated the presence of aggregates in the structure due to extensive π ··· π stacking of the aromatic core 11b. A similar fluorescence quenching mechanism was also reported in metal‐organic compounds 12a–12c.…”
Section: Resultssupporting
confidence: 63%
“…The polyimides of perylene and naphthalene bisimides reported in the literature are however not very high because of the inherent low solubility of the formed polymer. 39 Therefore, the inherent viscosity of 0.2 dL/g reported here indicated reasonably high molecular weight and the perylene containing polymers were obtained as dark red powders. Supporting Information Figure S4 shows the TGA thermograms of the homo-and copolymers, and the 10% weight loss temperatures are given in Table 1.…”
Section: Resultsmentioning
confidence: 58%
“…Such insolubilities have been reported 24,37 for these types of systems, and we expect to solve this problem in the future through the use of a more solubilizing soft segment. 26…”
Section: Molecular Weightsmentioning
confidence: 99%
“…In addition to preliminary synthetic work, we present the optical and thermal characterization of the resulting polymeric materials. Recent work has examined the incorporation of functional electronic units such as 3,4‐ethylenedioxythiophene (EDOT) monomer, rylene diimides, and oligophenylene vinylenes into polyurethane‐type materials 19, 24–26. The pi systems embedded within the macromonomers here consist of a series of telechelic oligothiophene diols and diamines as chain extenders for complex polymer synthesis.…”
Section: Introductionmentioning
confidence: 99%